TEACHERS’ CHALLENGES IN IMPLEMENTING DIFFERENTIATED LEARNING FOR STUDENTS OF JUNIOR HIGH SCHOOL LEVEL IN PALEMBANG - Muhamad Chalik Chairuman; Annisa Astrid; Deta Desvitasari (Wiralodra English Journal, 2025)
This study explores the challenges an English teacher faces in implementing differentiated learning within the framework of the Emancipated Curriculum in a junior high school in Palembang. Using a qualitative case study approach, data were gathered through interview and observation. The findings identified five main problems: difficulties in assessing students; limited planning time; large class sizes; technical disruptions during lessons; and the need for ongoing professional development. Although the teacher demonstrated a strong understanding of differentiation, enhanced through the Teacher Mover program, implementation remained difficult without sufficient support. This study highlights the importance of institutional support, reliable infrastructure, and effective assessment tools to ensure meaningful and sustainable application of differentiated learning. The findings suggest that while teacher commitment and training are crucial, systemic support plays an equally vital role. Further research involving more participants or schools is recommended to deepen understanding and broaden perspectives on differentiated learning practices in Indonesian EFL contexts.